Setup for photolithography on microscopic flakes of 2D materials by combining simple-geometry mask projection with writing - Jindal, Vishwas; Sugunakar, Vasam; Ghosh, Sandip (Review of scientific instruments, 2022)
An optical arrangement and procedure for photolithography on microscopic flakes of two-dimensional materials with an arbitrary shape/size is described. The technique combines projection of demagnified images of simple geometry macroscopic masks with writing. Only a few masks, such as vertical/horizontal slit and square hole, are sufficient to generate most of the required patterns. The setup allows for initially locating the photoresist coated flake on a substrate by imaging it. Thereafter, the automated precise sample stage motion followed by projection of the demagnified mask image is repeated several times to expose the photoresist in the shape of the required pattern. Appropriate light wavelength regimes for imaging and for exposure are chosen through automated optical filter switching. Programming steps for the process are described. The setup allows for direct lithography in one round on microscopic samples without requiring sample shape/size specific masks or predefined position markers. Making of electrode lines of width down to 3 μm, at desired locations on tiny flakes of MoS2, is demonstrated.